Corporate Social Responsibility And Financial Ratio on Market Value Added - Diyah Santi Hariyani; L. H. Almira Salatnaya; D.Dwi Mardani (Ilomata International Journal of Tax and Accounting, 2020)
The purpose of this study is to empirically examine the Effect of Corporate Social Responsibility (CSR) and Financial Ratio on Market Value Added (MVA), both simultaneously and partially. This research was conducted using a sample of 33 companies winning 2016 CSR and Top CSR 2017 Appreciation by determining their samples (purposive sampling) because there were certain considerations over a period of 2 years (2015-2016). The results of this study indicate that simultaneously the effect of CSR and Financial Ratio together does not significantly influence Market Value Added (MVA). And partially ISO9001, ISO14001, ISO26000, OHSAS18001, Current Ratio (CR), Debt to Equity Ratio (DER), Price Earnings Ratio (PER), Total Asset Turnover and Return on Sales do not significantly influence MVA. While partially only ESOP has a significant effect on MVA.